Urbanization requires brick production. A case study from the Kathmandu Valley, Nepal - Gutschow, Niels; Kreutzmann, Hermann (ERDKUNDE, 2002)
The urbanization process in Nepal is to be distinguished from urban developments in neighbouring South Asian countries and remains a specific case linked to the political frame conditions in time. The paper offers a historical reconstruction of urban development in Nepal and discusses urban planning efforts and recent developments which seem to be detached from these. The case study emphasizes the quantitative and qualitative changes in brick production in Nepal while studying one annular kiln and its production system in detail. The kiln and the work performance of the people involved correlate to a system of production which has undergone tremendous changes since traditional craftsmanship was replaced by semi-professional migrant labourers. Brick production in the Kathmandu Valley is linked to contributing commodities and people from the East and West of Nepal and from India. All participants profit from brick production in rather varied ways. The ever-growing demand for construction material reflects the rapid growth of urban settlements in vertical and horizontal dimensions as well as the competition between brick production and agriculture when it comes to spatial utilization in the vicinity of towns and cities.